Modelling the greenhouse environment and the growth of cucumbers (Cucumis sativus L.) : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Agricultural Engineering at Massey University - Wells, Colin Mark (Massey University, 1992)
Mathematical models which describe the greenhouse environment, and the growth of a crop of cucumbers, in that environment, have be en developed and tested. The models have been used to predict: the response of the greenhouse to varying weather conditions, the growth of the crop leaf canopy, and the weight and number of fruit harvested The greenhouse environment has been modelled using a system of non-linear differential equations, derived from a consideration of the energy and mass balances of the glazing, internal structure, crop canopy, root media, fl oor, deep soil layers, and the greenhouse air space. The equations have been solved for five minute time steps, using measured values of outside weather conditions and control inputs as boundary values. Entry of solar radiation into the greenhouse, and absorption by various surfaces, has been determined using transmission tables generated using a "ray-tracing" light transmission model. The light transmission model has been calibrated in a separate experiment. The incoming solar radiation has been partitioned between diffuse, direct, photosynthetically active and near infra-red radiation, for use in the crop model. Validation experiments have been performed to test the greenhouse environment simulation model. The results of the validation exercise showed that the model was capable of predicting the temperatures in the greenhouse, within a few degrees. The mean errors were smaller for the crop canopy, root medium, and floor, than for the glazing or air temperature. Prediction errors for relative humidity and carbon dioxide concentration were more variable. An existing model of cucumber development rate, and leaf expansion, has been modified and validated. This gave good results when adequate account was taken of leaf senescense, and initiation of lateral growths. Sub-models for photosynthesis, respiration, and assimilate partitioning have been develope d , and c ombined with the greenhouse environment and leaf expansion models. The combined model has been used to predict the course of growth of a cucumber crop over one growing season, and the number and weight of fruit harvested. The predictions have been compared to results from a test crop. This revealed that while the total number of fruit harvested was accurately predicted, the total weight of harvested fruit was not. The models are intended to be used in the s tudy of optimal control of the greenhouse environment.
Keywords: Greenhouse environment; Cucumber; Cucumis sativus; Greenhouse management